Culturally Sensitve Maternal Health Promotion Messages - Omoloso, Aisha Imam; Ahmad, Mohd Khairie; Ramli, Romlah (2017)
Identification and understanding of the target audience have significant implications for the production of culturally sensitive and relevant health promotion messages capable of achieving effective outcomes.Yet, despite growing global concern on the utilisation of culture and context- based approaches in addressing health issues, research harnessing the role of the audience in the development of culturally sensitive and relevant maternal health promotion messages is limited in Nigeria.This study explores the lived maternal health promotion experiences of pregnant and post natal women in north central Nigeria.In-depth phenomenological interviews were conducted with 29 perinatal women of diverse ethnicity to understand their maternal health experiences and health promotion concerns.NVivo 11 software was used to manage data.Findings indicate that multiple sources of information utilised by the women could prompt either healthy or harmful practices while messages can be culturally sensitive by targeting relevant opinion leaders and change agents appropriate messages.